Global asymptotic stability of Cohen - Grossberg neural networks of neutral type - Akca, H.; Covachev, V.; Covacheva, Z. (Нелінійні коливання, 2014)
Sufficient conditions for existence and global asymptotic stability of a unique equilibrium point of a Cohen – Grossberg neural network of neutral type are obtained. An example is given. Отримано достатнi умови iснування та глобальної стiйкостi єдиної точки рiвноваги для нейронної мережi Коена – Гроссберга нейтрального типу.